Long-term follow up of single-incision laparoscopic cholecystectomy compared to conventional laparoscopic cholecystectomy - Hayder Shabana; Abdul-Karim Abbas; Darragh Grace; Jeremy Kay Hock Lee; Colm J O'Boyle (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Purpose: Conventional Laparoscopic Cholecystectomy (CLC) is the "gold standard" approach for patients with gallstones. Single-incision Laparoscopic Cholecystectomy (SILC) was an alternative technique, purportedly offering several postoperative benefits over CLC. Studies comparing short-term postoperative outcomes of SILC versus CLC have yielded conflicting results. Our paper aims to compare the long-term postoperative outcomes of patients undergoing SILC and CLC with a minimum follow up of seven years. Methods: A comparative retrospective study between SILC and CLC was conducted among 118 patients undergoing cholecystectomy from October 2008 to December 2010 (SILC=67/CLC=61). An initial retrospective chart review was performed. We later surveyed the patients who had undergone cholecystectomy by telephone interview at a mean(sd) of 4(0.75) years, and at 8(0.75) years. Postoperative outcomes were evaluated.  Results: No significant difference between SILC and CLC groups for daily pain scores (p = 0.45 and 0.97, for day 1 and 2, respectively), daily narcotic requirements (p = 0.09 and 0.85, for day 1 and 2, respectively), and time to return to normal activity (p = 0.11). The mean(sd) operative time was greater in SILC group [52(2.0) mins versus 36(2.3) mins; p <0.05]. There was a shorter mean(sd) length of stay postoperatively in the SILC group [2(0.11) days versus 3(0.32) days; p <0.05]. The SILC group had a higher median(sd) cosmetic satisfaction score (IQR) than the CLC group at both the intermediate-term [10(10) versus 9(8 to10); p <0.05] and long-term [10(10) versus 9(9to10); p <0.05] follow up. Conclusion: SILC is associated with higher patient cosmetic satisfaction than CLC.  However, the procedure is more technically challenging and associated with increased operating time and costs. The marginal cosmetic benefit at the expense of increased operative time and economic costs will likely mean that the choice of procedure will be largely patient rather than physician driven.